Wild pigs and their widespread threat to biodiversity conservation in South America - la Sala, Luciano Francisco (2023)
Wild pigs, including wild boar (Sus scrofa) and feral domestic pig (Sus scrofa domestica), are associated with negative impacts in their native and introduced ranges. We compiled wild pig occurrence reports and utilized Maximum Entropy modelling to predict their potential distribution in ecoregions overlaying Argentina, Brazil, Bolivia, Chile, Uruguay and Paraguay. An analysis of their observed and potential distributions was carried out in relation to four biodiversity hotspots and 3766 protected areas to estimate the number of units and percent area currently and potentially invaded. Among biodiversity hotspots, Atlantic Forest, Cerrado, and Chilean Winter Rainfall-Valdivian Forests included 44.7% of wild pig records. The proportion of suitable area was 85% in Atlantic Forest, 61.3% in Cerrado, 37.5% in Chilean Winter Rainfall-Valdivian Forests, and 5.6% in Tropical Andes. The number of protected areas with known wild pig presence was led by Uruguay (100%), followed by Chile (20.3%), Argentina (15.8%), Paraguay (9.5%), Bolivia (6.5%), and Brazil (4.7%). The proportion of protected areas with predicted wild pig presence was highest in Uruguay (100%), followed by Paraguay (72.6%), Brazil (58.0%), Argentina (57.4%), Chile (42.2%), and Bolivia (35.9%). Our work represents the first assessment of wild pig potential distribution in South America and highlights the potentially devastating impacts of wild pigs on the regional biodiversity and national conservation targets, especially at mega-diverse areas. We present a dynamic web application that can be readily consulted by scientists, managers and decision makers to improve wild pig control and risk mitigation actions in the study region.